Penentuan calon mahasiswa penerima beasiswa hafiz Alquran pada tingkat perguruan tinggi menggunakan metode SMART - Hamidani, Syafi’ul; Amalia, Veradilla (TEKNOLOGI: Jurnal Ilmiah Sistem Informasi, 2020)
STMIK Bina Nusantara Jaya as one of the universities in the city of Lubuklinggau, South Sumatra, which provides scholarships for Al-Qur'an hafiz in that city to take full courses. Currently, the process of determining prospective scholarship recipients is still using a computer application, namely Microsoft Excel. With the large number of applicants who registered, the limited human resources who handled the determination of the recipients of this scholarship, and the very limited quota, it made it difficult for STMIK Bina Nusantara Jaya to determine better priorities for prospective students who received the hafiz Al-quran scholarship. For this reason, this study is intended to assist the STMIK Bina Nusantara Jaya in selecting students who receive the hafiz Al-qur'an scholarship based on 4 criteria, namely memorizing the Al-qur'an, high school academic scores, the work of parents and dependents of the parents, from these criteria. the calculation will be carried out using the Simple Multi Attribute Rating Technique (SMART) method. This method was chosen because of its simplicity of calculation and ease of finding the best alternative by assigning a weighting value from 0 to 100 in the criteria so as to simplify the calculation process to obtain the best alternative. This study resulted in recommendations for determining prospective scholarship recipients by 80%.